Orígenes y evolución de las agrupaciones de vivienda en altura (2017)
The article addresses the topic of housing groups in height. In the introduction, the object of study is limited, and the effect of “closed sets” on urban life is analyzed. The confinement of users as well as the perception of invisible (and visible) boundaries are highlighted in city. As methodology is established the systematic and historical review of housing groups in height in a window of time spanning 20 centuries. The results include the projects of housing in height that gathers the history of urbanism, especially in Europe, and a selection of this type of groupings in the city of Bogota, generating an itinerary that allows to observe with clarity the origins and the evolution of the groupings of housing in height, since the Roman insulae to the closed sets that now abound in Latin American cities.